Help..this is where I am lost!!!
Solve the following equation for the unknown, x.
(1-2x) - 3(4+5x) +6(7-8x) = 0
1-2x-3(5x+4)+6(-8x+7)=0
2x-3(5x+4)+6(-8x+7)+1=0
-2x-3*5x-3*4+6(-8x+7)+1=0
-
-2x-15x-12+6(-8x+7)+1=0
-
2x-15x+6(-8x+7)+(-11)=
(-2-15)x+6*8x)-6*7-11=0
-17x-48x+42-11=0
-65x+31=0
x=31/65
Solve the following equation for the unknown, x.
(1-2x) - 3(4+5x) +6(7-8x) = 0
1-2x-3(5x+4)+6(-8x+7)=0
2x-3(5x+4)+6(-8x+7)+1=0
-2x-3*5x-3*4+6(-8x+7)+1=0
-
-2x-15x-12+6(-8x+7)+1=0
-
2x-15x+6(-8x+7)+(-11)=
(-2-15)x+6*8x)-6*7-11=0
-17x-48x+42-11=0
-65x+31=0
x=31/65